THE ABILITY IMPROVEMENT OF THE ADOLESCENT DRAMA SCRIPT WRITING FOR SECOND GRADE STUDENTS OF MAN 2 BANDA ACEH THROUGH COOPERATIVE LEARNING METHODS WITH THE TYPE OF PAIREDSTORYTELLING - Khairiah Khairiah (Master Bahasa, 2019)
This research aimed to determine the ability improvement of the adolescent drama script writing for second grade students of MAN 2 Banda Aceh through cooperative learning methods with the type of pairedstorytelling. The method used in this research is the experimental method with a quantitative approach. Quantitative approach is used to describe the ability of the adolescent drama script writing students who obtain the cooperative learning approach with the type of paired storytelling, and to describe the results of the adolescent drama script writing with conventional approaches. This research involved 60 students consisting of two classes, as 30 students in the experimental class taught by the cooperative method and 30 students in the control class taught by conventional methods. Quantitative approach needs to be done in the form of research design pretest-posttest control group design. The results of this research indicate that the cooperative method with the type of paired storytelling can improve the ability of the second grade students of MAN 2 Banda Aceh in the adolescent drama script writing. Based on the analysis it can be concluded that the ability of students in the adolescent drama script writing acquired from cooperative learning through paired storytelling methods is better than the students who received the learning of the adolescent drama script writing through conventional methods.